Mechanical, electrical and microstructural characterisation of multifunctional structural power composites. (June 2015) - Greenhalgh, ES; Ankersen, J; Asp, LE; Bismarck, A; Fontana, QPV; Houlle, M; Kalinka, G; Kucernak, A; Mistry, M; Nguyen, S; Qian, H; Shaffer, MSP; et al.
Multifunctional composites which can fulfil more than one role within a system have attracted considerable interest. This work focusses on structural supercapacitors which simultaneously carry mechanical load whilst storing/delivering electrical energy. Critical mechanical properties (in-plane shear and in-plane compression performance) of two monofunctional and four multifunctional materials were characterised, which gave an insight into the relationships between these properties, the microstructures and fracture processes. The reinforcements included baseline T300 fabric, which was then either grafted or sized with carbon nanotubes, whilst the baseline matrix was MTM57, which was blended with ionic liquid and lithium salt (two concentrations) to imbue multifunctionality. The resulting composites exhibited a high degree of matrix heterogeneity, with the ionic liquid phase preferentially forming at the fibres, resulting in poor matrix-dominated properties. However, fibre-dominated properties were not depressed. Thus, it was demonstrated that these materials can now offer weight savings over conventional monofunctional systems when under modest loading.